Ice cream as a vehicle for incorporating health-promoting ingredients: conceptualizationand overview of quality and storage stability aspects - Soukoulis, Christos; Fisk, Ian D.; Bohn, Torsten (Wiley, 2014)
Ice cream is a product with peculiar textural and organoleptic features and is highly appreciated by a very broad spectrum of consumers. Ice cream’s structure and colloidal design, together with its low-temperature storage, renders it a very promising carrier for the stabilization and in vivo delivery of bioactive compounds and beneficial microorganisms. To date, many applications related to the design and development of functional ice cream have been documented, including products containing probiotics, prebiotics, synbiotics, dietary fibers, natural antioxidants such as polyphenols, essential and polyunsaturated fatty acids, and low glycemic index blends and blends fortified with mineral or trace elements. In this review, promising strategies for the incorporation of innovative functional additives to ice cream through the use of techniques such as microencapsulation, anoemulsions, and oleogels are discussed, and current insights into the implications of matrix, processing, and digestion on bioactive compounds in frozen dairy desserts are comprehensively reviewed, thereby providing a holistic overview of the current and emerging trends in this functional food sector.